پرسیاری زنجیره‌یی و ڕۆڵی له‌ دەرخستنی زانیارییه‌كان - دزه‌یی, پ.د.عبدلواحد مشیر; حامد, ڕه‌شاد بكر (Sulaimani Journal for Humanities, 2024)
The title of the study is (Probing question and role in revealing information). The importance of the study is that the questioner will benefit from receiving the necessary information from recipients who do not provide information and use filters in their speeches, and research that has been conducted under the method of analysis. Mita's language is a great process for returning filtered information, and the information is detailed and logistical, far from doubt, emotions, which are done through chain questions, which mita language itself sources from questioning. The content of the research is divided into two parts: the first part, specific to the sequential question ingenuity and includes the following topics: question meth, sequential question meth, sequential question action. The second part is specific to serial questions and filtering, which includes filtering and avoiding answers, forms of information filtering, questions and chains for restore and information organization. At the end of the study, the results of the study and the list of sources are presented.